2021
DOI: 10.3390/jpm11060579
|View full text |Cite
|
Sign up to set email alerts
|

A Type 2 Ryanodine Receptor Variant in the Helical Domain 2 Associated with an Impairment of the Adrenergic Response

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is triggered by exercise or acute emotion in patients with normal resting electrocardiogram. The major disease-causing gene is RYR2, encoding the cardiac ryanodine receptor (RyR2). We report a novel RYR2 variant, p.Asp3291Val, outside the four CPVT mutation hotspots, in three CPVT families with numerous sudden deaths. This missense variant was first identified in a four-generation family, where eight sudden cardiac deaths occurred before the age of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The RyR2 mutation associated with idiopathic ventricular fibrillation confirmed as a loss-of-function mutation exhibiting Ca 2+ release deficiency ( 66 ). However, a recent study identified a loss-of-function mutation D3291V, which markedly reduced luminal Ca 2+ sensitivity, and blunted response to adrenergic stimulation, also exhibiting a CPVT phenotype ( 116 ). The relationship between gain-of-function or loss-of-function and the clinical phenotype still needs to be elucidated ( 117 ).…”
Section: Genetic Factors Of Ventricular Arrhythmias Without Structura...mentioning
confidence: 99%
“…The RyR2 mutation associated with idiopathic ventricular fibrillation confirmed as a loss-of-function mutation exhibiting Ca 2+ release deficiency ( 66 ). However, a recent study identified a loss-of-function mutation D3291V, which markedly reduced luminal Ca 2+ sensitivity, and blunted response to adrenergic stimulation, also exhibiting a CPVT phenotype ( 116 ). The relationship between gain-of-function or loss-of-function and the clinical phenotype still needs to be elucidated ( 117 ).…”
Section: Genetic Factors Of Ventricular Arrhythmias Without Structura...mentioning
confidence: 99%